2008
DOI: 10.1007/s11743-008-1104-4
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and Localization of Fragrances in Surfactant Mixed Micelles

Abstract: The localization and dynamics of fragrance compounds in surfactant micelles are studied systematically in dependence on the hydrophobicity and chemical structure of the molecules. A broad range of fragrance molecules varying in octanol/water partition coefficients P ow is employed as probe molecules in an aqueous micellar solution, containing anionic and nonionic surfactants. Diffusion coefficients of surfactants and fragrances obtained by Pulsed Field Gradient (PFG)-NMR yield the micelle/water distribution eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 44 publications
9
53
1
Order By: Relevance
“…This is consistent with previous observations from the surface adsorption of surfactant/perfume mixtures [30] and on the impact of perfumes on surfactant self-assembly [9,26,[36][37][38]. Furthermore, the variation in the scattering length densities of both the alkyl chain and headgroup regions, for d-LAS-6/h-perfume and h-LAS-6/d-perfume, is consistent with that interpretation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with previous observations from the surface adsorption of surfactant/perfume mixtures [30] and on the impact of perfumes on surfactant self-assembly [9,26,[36][37][38]. Furthermore, the variation in the scattering length densities of both the alkyl chain and headgroup regions, for d-LAS-6/h-perfume and h-LAS-6/d-perfume, is consistent with that interpretation.…”
Section: Discussionsupporting
confidence: 93%
“…The more hydrophilic phenylethanol is predominantly solubilized into the headgroup region. These different locations are consistent with the observations associated with surfactant self-assembly and perfume solubilization [9,26,35]. The differences in location result in the surface multilayer structures existing over a wider range of surfactant/perfume compositions for phenylethanol than for linalool.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In fact, very hydrophobic molecules are located at the interior of the micellar core, whereas linear primary alcohols possess an amphiphilic character and can insert themselves into the interface of the surfactant palisade layer [5][6][7]. For example, it has been shown that a terpenic alcohol leads to micellar swelling in an all purpose cleaner formulation, which is a direct consequence of the chemical structure of the molecule and cannot be explained by the log P value [8].…”
Section: Introductionmentioning
confidence: 99%